Henri Oguike Dance Company Review - Roy, Sanjoy (Dance Books Ltd., Alton,Hampshire (UK), 2003)
PALABRAS CLAVE: Henri Oguike Dance Company, Front Line, Melancholy Thoughts, f.p.s. (frames per second), Dido & Aeneas.
Dentro del apartado "Dance Now. Short Takes".